THE EFFECT OF FIXED ASSETS VALUE, REGIONAL ORIGINAL INCOME AND CAPITAL EXPENDITURES ON MAINTENANCE EXPENDITURES IN THE DISTRICT/CITY OF SOUTH SUMATRA PROVINCE - Melda Novri Andini; Kiagus Zainal Arifin; Nurhasanah Nurhasanah (Indonesian Journal of Multidisciplinary Science, 2022)
The government gives freedom to each region to regulate its own government affairs, including the distribution of development funds with the aim of maintaining the continuity of government and improving the quality of public services. The allocation of capital expenditures related to adequate maintenance expenditures is very important to maintain the state of government assets so that they can function properly. Every year, various government work units have budgeted the allocation. However, the allocated budget is sometimes too large, resulting in excess funds and cannot be maximized for other priority expenditures. The purpose of this study is to determine the effect of Fixed Assets partially on Maintenance Expenditure. The research method is basically a scientific way to obtain data with certain purposes and uses.” The type of research used in this research is quantitative method. Quantitative research methods can be defined as research methods based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, statistical quantitative data analysis, with the aim of testing hypotheses that have been determined. In accordance with the provisions of the Decree of the Minister of Finance of the Republic of Indonesia Number 01/KM.12/2001 concerning Guidelines for Capitalization of State Owned Assets in the Government Accounting System as regulated again through Minister of Finance Regulation Number 181/PMK.06/2016 concerning Administration of State Owned Goods, the condition of fixed assets is grouped into good, lightly damaged and heavily damaged. Conclusion: Partially Fixed Asset Value (X1) has no effect and is not significant on Maintenance Expenditure (Y) in the Regency/City of South Sumatra Province. Regional Original Income (X2) has no effect and is not significant on Maintenance Expenditures in the Regency/City of South Sumatra Province.